Influence of growth hormon (rhGH) and Biolaminin 521LN on proliferative activity of stem cells of cat - Мазуркевич, А. Й.; Ковпак, В. В.; Ковпак, О. С. (Scientific Progress & Innovations, 2018)
The usage of cell technology in clinical practice requires a large amount of cell material. It in turn provokes the development of methods that will allow to obtain a greater amount of cell material for a much shorter period of time. According to literary sources it is known that the growth hormone and the Biolaminin LN 521 can have a positive influence on the mitotic activity of stem cells. Considering the differences in the cell composition of the cell cultures obtained from different tissues, the effects of recombinant human growth hormone (rhGH) and Biolaminin 521 LN will be different. Therefore, our aim was to study the effects of recombinant human growth hormone (rhGH) in various concentrations and to study the Biolaminin LN 521 for the proliferative activity of stem cells obtained from bone marrow, adipose tissue and cardiac muscle of cat. The effects of recombinant human growth hormone (rhGH) in various concentrations and the effects of Biolaminin LN 521 for proliferative activity and genetic stability of stem cells obtained from bone marrow, adipose tissue and cardiac muscle of cat were studied. It was found that the growth hormone has a positive effect on the proliferative activity of stem cells in cell cultures of adipose tissue and cardiac muscle of cat at low concentrations (10 ng/ml), while the effect on the cell culture of bone marrow stem cells was the opposite. According to the cytogenetic analysis it was found that adding recombinant human growth hormone to the culture media does not lead to a significant increase in the number of genetic errors, while adding the Biolaminin 521 LN leads to a decrease in the number of cells with altered karyotype (in comparison with control) in all the studied cell cultures.